(3MOjK GdCdas - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai cKQ GdSDGd Yf GdMOjK GdeTJgQ Ydi CdSfI GdfGS Cf GdfHj Udi Gddg Ydjg hSde dG jecK aj GdbHQ Cda SfI hCLjH HCfg HGWd dG CUd dg Ke LGAfj QLd ef GdCYjGf dG CSejg aj gPg GdSfI aj TgQ QHjY hgj SfI KeGf hSHYjf hKeGfeGFI heYg hQbIs
(3BNQgG (B:s
(3ajbhdhf eG fHZj ZfjeI CaVd ef gPg ajQLYhf hjNQL GdeSdehf aj BKGQge MJi jOQchge ajgRe Gddg GdLjT ajbJdge GdeSdehf hjCSQhge hCNQL fYje Hf YHO Gddg Hf YeQ hbGd djCJjfce Cgd GdCfOdS hGdMeO ddgs
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs